Hubungan IMT Terhadap Kebugaran Kardiorespirasi Pada Mahasiswa Dengan Obesitas Sentral Di FKIK UNWAR - Gede Bagus Dwipayana Putra Dewa; Tanjung Subrata; Asri Lestarini (Aesculapius Medical Journal, 2024)
[The Correlation Between BMI and Cardiorespiratory Endurance in FKIK UNWAR Student with Central Obesity] The Correlation Between BMI and Cardiorespiratory Endurance in FKIK Unwar Student with Central Obesity Cardiorespiratory endurance is the ability of the heart, lungs, and blood vessels in providing oxygen for muscle performance during rhythmic and sustained activity. Body Mass Index (BMI) is one of the factors that can affect the level of cardiorespiratory endurance. However, this measurement cannot measure the proportion of body fat as in someone with central obesity. A person with normal BMI can have a proportion of body fat > 30%, and if distributed as visceral fat will have a high association with cardiometabolic risk. The purpose of this study was to determine the relationship between BMI and cardiorespiratory endurance in Faculty of Medicine and Health Sciences Warmadewa University student with central obesity. The design of this study was observational analytic with cross sectional approach. This study was conducted on 60 students with central obesity. Body Mass Index was measured using equation body weight (kg)/the square of height (m), while the level of cardiorespiratory endurance was measured using Harvard Step Up Test. The data was analyzed by Statistical Package for Social Science (SPSS) 18.0 for Windows program. The correlation between both variable were analyzed by Spearman correlation test. The results was showed as follow: the average score Weist Circumference, BMI and cardiorespiratory endurance were 91,0±8; 29.01±3.01; and 18.61±8.40, respectively and the correlations between both were negatif (p=000 and r=0.51). The conclusion could be drawn that there was significance correlation between BMI and cardiorespiratory endurance. It was recommended that the students with central obesity should be improved the physical activity regularly